Bank's strategies during the financial crisis - Maria Cristina Recchioni; Gabriele Tedeschi; Simone Berardi (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
In this paper we introduce a calibration procedure suitable for the validation of agent based models. Starting from the well-known financial model of Brock and Hommes 1998, we show how an appro- priate calibration technique makes the model able to describe price time series.The calibration results show that the simplest version of the Brock and Hommes model, with two trader types, fundamentalists and trend-followers, well replicates the price series of four sub-sectoral banking indexes, representing different geographical areas. Moreover, we show how the parameter values of the calibrated model are important to analyse the trader behavior on the different investigated markets.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C52; C63; G15; 330; Validation; Agent-based models; Asset pricing; Heterogeneous beliefs